Kajian Kemampuan Maksimum Danau Sentani Dalam Mereduksi Banjir Di DAS Sentani - Fauzi, Mohammad; Rispiningtati, Rispiningtati; Hendrawan, Andre Primantyo (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
Lake Sentani which located at Jayapura Regency is known as one of largest and most beautiful lakes in the province of Papua . About 14 rivers is flowing into Lake Sentani, thus one of its main functions is as a flood catchment. Based on the research conducted by Balai Wilayah Sungai Papua in 2012, it can be measured that the capacity of Lake Sentani is equal to 4.821.49 million m .The aim of this research is to analyze the flood discharge into Lake Sentani caused by land use changes from the use for every 3 years (2007, 2010 and 2012). The simulation of the flood discharge at the outlet and flood routing was made using the Muskingum method.From the analysis, it is shown that the discharge at outlet (Qout) was less than the discharge from inflow (Qin) as a result of simulation. The flood reduction (which was formed as a percentage) can be calculated as a ratio between the differences of (Qin - Qout) and inflow discharge (Qin). By this formula, it can be calculated that the average of flood reductions were 86,18% (2007), 86,22% (2010) and 86,23% (2012), by using simulation from eight different Return Period Discharge (Q2 to Q1000). Thus it can be concluded that Lake Sentani still has an adequate capacity to reduce flooding from the upstream zone of Sentani Catchment Area.From the results, it is found that the flood discharge is affected by the changes of catchment area and land use. Under these changes, the runoff coefficient will be changed as well.Keywords: Maximum Capacity, Flood Discharge, Flood Reduction